Advances in Manufacturing II Volume 5 - Metrology and Measurement Systems - Diering, Magdalena; Wieczorowski, Michał; Brown, Christopher A. (Lecture Notes in Mechanical Engineering,, 2019)
This book gathers timely contributions on metrology and measurement systems, across different disciplines and field of applications. The chapters, which were presented at the 6th International Scientific-Technical Conference, MANUFACTURING 2019, held on May 19-21, 2019, in Poznan, Poland, cover cutting-edge topics in surface metrology, biology, chemistry, civil engineering, food science, material science, mechanical engineering, manufacturing, metrology, nanotechnology, physics, tribology, quality engineering, computer science, among others. By bringing together engineering and economic topics, the book is intended as an extensive, timely and practice-oriented reference guide for both researchers and practitioners. It is also expected to foster better communication and closer cooperation between universities and their business and industry partners. .